2021
DOI: 10.1016/j.ssmmh.2021.100001
|View full text |Cite
|
Sign up to set email alerts
|

Order out of chaos: Sense of coherence and the mediating role of coping resources in explaining mental health during COVID-19 in 7 countries

Abstract: In the midst of the COVID-19 pandemic and the universal chaos created by it, this study explores the role of sense of coherence (Soc, Antonovsky, 1979) and how it enables coping with a stressful situation and staying well. SOC is a generalized orientation which allows one to perceive the world as comprehensible, manageable, and meaningful. In an attempt to understand ‘how does the SOC work’ we employed the salutogenic assumption that a strong SOC allows one to reach out in any given situation and find those re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
32
3
1

Year Published

2021
2021
2022
2022

Publication Types

Select...
3
3
1

Relationship

1
6

Authors

Journals

citations
Cited by 28 publications
(39 citation statements)
references
References 32 publications
3
32
3
1
Order By: Relevance
“…SOC helps to identify and mobilize relevant resources to cope with stressors and manage tension successfully and, as a result of this process, it preserves health and well-being. Previous studies have confirmed the important role of SOC in predicting health in different kinds of crises (for review, see Eriksson and Mittelmark, 2017 ) and in the beginning of the COVID-19 pandemic ( Schäfer et al, 2020 ; Mana et al, 2021a , b ). This study, however, deepened our insight regarding the potential longitudinal effects of the individual resource SOC in the unique global context of the pandemic actually having transformed the whole world to an unpredictable and chaotic place for a very long time ( Žižek, 2020 ).…”
Section: Discussionmentioning
confidence: 80%
See 1 more Smart Citation
“…SOC helps to identify and mobilize relevant resources to cope with stressors and manage tension successfully and, as a result of this process, it preserves health and well-being. Previous studies have confirmed the important role of SOC in predicting health in different kinds of crises (for review, see Eriksson and Mittelmark, 2017 ) and in the beginning of the COVID-19 pandemic ( Schäfer et al, 2020 ; Mana et al, 2021a , b ). This study, however, deepened our insight regarding the potential longitudinal effects of the individual resource SOC in the unique global context of the pandemic actually having transformed the whole world to an unpredictable and chaotic place for a very long time ( Žižek, 2020 ).…”
Section: Discussionmentioning
confidence: 80%
“…An additional study explored “how does SOC work” during the COVID-19 pandemic and tested the salutogenic assumption that a strong SOC allows one to reach out in any given situation and find those resources appropriate to the specific stressor ( Mana et al, 2021a ). Data collected among participants from seven countries confirmed the suggested mediation model and revealed that perceived family support and trust mediated the relationships between SOC and mental health, controlling for gender, level of exposure to the virus, and level of health and financial risk ( Mana et al, 2021a ).…”
Section: Introductionmentioning
confidence: 99%
“…As SOC is frequently discussed as a resilience factor [22,30,31], several studies have investigated SOC in the context of the COVID-19 pandemic [32][33][34][35][36][37][38][39]. A recent study showed a robust crosssectional relationship between SOC and mental health across six countries during the first wave of the pandemic [35]. This finding is supported by a large number of cross-sectional studies conducted during the first wave [32][33][34]36,37,40] and fewer studies carried out during the second wave [38,39] of the pandemic.…”
Section: Introductionmentioning
confidence: 93%
“…As SOC is frequently discussed as a resilience factor [22,30,31], several studies have investigated SOC in the context of the COVID-19 pandemic [32][33][34][35][36][37][38][39]. A recent study showed a robust crosssectional relationship between SOC and mental health across six countries during the first wave of the pandemic [35].…”
Section: Introductionmentioning
confidence: 99%
“…This chaotic global pandemic, however, was also an opportunity to explore salutogenic concepts like SOC and SONC and to understand their roles not only in promoting health but also beyond health, as potential factors in increasing some order out of the chaos. Mana and Sagy, jointly with the Global Working Group on Salutogenesis, conducted some international research (Mana, Bauer, et al, 2021;Hardy et al, 2021;Mana, Super et al, 2021;. The theoretical basis of the salutogenesis, and its fundamental philosophical postulate that the world is chaotic in its nature, was an appropriate basis for these studies.…”
Section: Salutogenesis and The Covid-19 Pandemic: Sociopolitical Considerationsmentioning
confidence: 99%